Synergistic Extraction of Lanthanides (III) with Mixtures of TODGA and Hydrophobic Ionic Liquid into Molecular Diluent. Issue 7 (10th November 2017) - Turanov, A. N; Karandashev, V. K; Khvostikov, V. A
ABSTRACT: The extraction of lanthanides(III) from aqueous nitric acid solutions with N, N, N', N' -tetra( n -octyl)diglycolamide (TODGA) and with mixtures of TODGA and the hydrophobic ionic liquid (IL) [C4 mim][Tf2 N] into 1, 2-dichloroethane (DCE) has been investigated. The extraction efficiency of Ln(III) ions was greatly enhanced by the addition of a small amount of IL to an organic phase containing TODGA. The synergistic effect comes from the higher hydrophobicity of Ln(III) extracted species formed by TODGA and the weakly coordinating Tf2 N − anions compared with those formed by TODGA and NO3 − ions as the counter-anions. The partition of Tf2 N − anions between the organic and aqueous phases is the dominant factor governing the extractability of lanthanides(III) with mixtures of TODGA and [C4 mim][Tf2 N]. The extraction of Ln(III) from aqueous nitric acid solutions by TODGA alone and its mixtures with [C4 mim][Tf2 N] into DCE can be described on the basis of the solvation extraction mechanism. However, in the extraction system with added [C4 mim][Tf2 N], the partition of Tf2 N − between two immiscible phases and the interaction between HTf2 N and TODGA in the organic phase should be taken into account. Possible reasons of the antagonistic effect in the TODGA–[C4 mim][Tf2 N] extraction system are discussed.